Exploring the impact of affordable housing finance on urban inclusivity: a structural equation modelling study of access, perception, and financial empowerment - Khasim Syed; Sachi Nandan Mohanty; Mukul Bhatnagar; Pawan Kumar; Rupa Khanna; Anuradha Jain (Frontiers in Sustainable Cities)
IntroductionThe creation of housing inclusivity is significant for uplifting the weaker section of society. The government has always taken relevant steps in developing nations to promote inclusivity in finance and housing for equitable national growth. This inclusion depends upon many parameters. There is a lack of comprehensive research addressing how existing housing policies and designs systematically exclude marginalized groups, highlighting a critical gap in achieving housing inclusivity. The present research focuses on creating a framework that integrates all such parameters to provide insight into which parameters should be given more importance and which should be given less importance during policy implications.MethodsTo achieve this, the research technique of PLS-SEM (Partial Least Squares Structural Equation Modelling) was employed in the present study. Mathematical calculations in the tool named SMART PLS 4 were based on the conceptual model to ensure the credibility of the framed model. The analysis was employed on the responses collected from the respondents using a constructed research instrument, which involves convenience sampling techniques and snowball sampling.ResultsUltimately, it can be inferred that government policies have the most significant impact on the financial improvement of low-income households, followed by perceptions of housing affordability and access to affordable housing finance.DiscussionThese findings have practical implications for government policy formulation, focusing on infrastructural development through loan assistance and regulatory support. Additionally, it is essential to provide tax incentives and necessary subsidies to the more vulnerable sections of society. Additionally, it is crucial to focus on financial empowerment through the cognition of efficient debt management to raise creditworthiness, as insinuated by the present research.